PENGARUH PELATIHAN KETERAMPILAN PERTOLONGAN PERTAMA PADA SISWA PINGSAN - Aji, Rustam; Marita, Zadam; Setyaningsih , Wiwik; Sulistiyani, Sulistiyani; Nulhakim, Lukman; Giatamah, Zuhrah; Anugrah, Anas Kiki (Media Penelitian dan Pengembangan Kesehatan, 2023)
The weather can cause fainting, every ceremony some students faint, first aid is taken to the UKS room. The better your knowledge about first aid, the better you will be at carrying out first aid measures in the field. One effort that can be made to increase knowledge related to first aid is by conducting skills training. The study aimed to improve first-aid skills for fainting students and determine the effect of training on first-aid skills for fainting students. Quasi Experiment Design, One Group Pretest-Posttest Design, one treatment group. The number of respondents was 30 people. The time of the research was September 2023. The research subjects were class III students at SDN 7 Rejang Lebong, with long experience as UKS members according to predetermined criteria. The research used primary data from class III students. Those who are willing and agree to become respondents. The statistical test results obtained by the correlation value through pre and post-produce a value of 0.428, a sufficient and positive relationship. The probability value/p value of the Paired T-test: Result = 0.123. Meaning: There is no difference between before and after treatment. Because the p-value is > 0.05 (95% confidence), there is no difference before and after implementation among research respondents the effect of first aid skills training on fainted students. It is recommended to plan regular training activities specifically for PMR on first aid for fainting students.